DYNAMICS OF REGIONAL EXPENDITURE BEFORE THE 2024 ELECTIONS - Defri Hardiansyah; Fauzan Misra (Journal of Economic, Bussines and Accounting (COSTING), 2026)
This study examines the dynamics of social assistance expenditure in Indonesian local governments ahead of the 2024 simultaneous regional elections, with a specific focus on district and city located on Sumatra Island. Drawing on the Political Budget Cycle and Public Choice Theory, this research aims to identify whether social assistance expenditure systematically increases in the pre-election period and whether incumbent candidacy strengthens this pattern. The study employs a quantitative approach using secondary data from district and municipal governments participating in the 2024 elections. A paired sample t-test is used to compare the proportion of social assistance expenditure in the non-election year (2022) and the pre-election year (2023), both for the full sample and for the subsample of incumbent-led regions seeking re-election. The findings reveal a statistically significant increase in the proportion of social assistance expenditure in the pre-election period, particularly in regions led by incumbents who re-contested. These results indicate the presence of a political budget cycle operating through discretionary and highly visible spending categories. The study contributes to the literature by providing subnational empirical evidence from Sumatra and highlighting the role , institutional discretion in shaping electoral fiscal behavior under Indonesia’s decentralized fiscal system.